2012
DOI: 10.1111/gcbb.12009
|View full text |Cite
|
Sign up to set email alerts
|

Nature of water‐biochar interface interactions

Abstract: A poplar biochar obtained by an industrial gasification process was saturated with water and analyzed using fast field cycling (FFC) NMR relaxometry in a temperature range between 299 and 353 K. Results revealed that the longitudinal relaxation rate increased with the increment of the temperature. This behavior was consistent with that already observed for paramagnetic inorganic porous media for which two different relaxation mechanisms can be accounted for: outer-and inner-sphere mechanisms. The former is due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

7
2

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 29 publications
6
86
0
Order By: Relevance
“…The 85% increase in pumpkin yield of the urine-biochar treatment compared with the biochar-only treatment must therefore be explained by further interaction effects of the cow-urine with the biochar. While a major part of the urine without biochar most probably leached out of the upper soil, the initial mixing of the urine with biochar retained nutrients in the porous biochar system [12,76,77].…”
Section: Resultsmentioning
confidence: 99%
“…The 85% increase in pumpkin yield of the urine-biochar treatment compared with the biochar-only treatment must therefore be explained by further interaction effects of the cow-urine with the biochar. While a major part of the urine without biochar most probably leached out of the upper soil, the initial mixing of the urine with biochar retained nutrients in the porous biochar system [12,76,77].…”
Section: Resultsmentioning
confidence: 99%
“…The discussion below is focused on the dry weight data and the number of nodules, whilst analysis related to the wet weights can be found in the SI ( Figure S2). have leached out [66,67]. Similarly, [66] demonstrates that adding co-composted biochar (at 2% dosage) to sandy-poor soil promotes biochar's positive effects on Chenopodium quinoa yield (by 305%) by nitrate capture and delivery.…”
Section: Biomass Yields For Maize (Zea Mays) Var Caatingueiromentioning
confidence: 92%
“…For instance, it is shown [26] that low-dosage cow-urine-biochar application to root zone in a fertile silt loam soil in Nepal resulted in a more than 300% increase in pumpkin yield as compared to treatment with urine only. When urine-biochar treatment was compared with a treatment of biochar only, an 85% increase in pumpkin yield was observed [26], which was explained by interaction urine with the biochar whereby urine without biochar might have leached out [66,67]. Similarly, [66] demonstrates that adding co-composted biochar (at 2% dosage) to sandy-poor soil promotes biochar's positive effects on Chenopodium quinoa yield (by 305%) by nitrate capture and delivery.…”
Section: Biomass Yields For Maize (Zea Mays) Var Caatingueiromentioning
confidence: 97%
“…Nieto et al (2016) reported an increase of air space volume of peat based growing substrates after addition with commercial charcoal and pruning waste biochar but only the latter lead to adequate water holding capacity and porosity values. Conte et al (2013) studying water-saturated poplar biochar suggested that water molecules are bound to the solid carbonaceous material through nonconventional hydrogen bonds: the comprehension of water-biochar interactions is fundamental to understand the molecular mechanisms through which water can be drained into biochar-amended substrates affecting their physical-chemical properties.…”
Section: Chemical and Physical Characteristics Of Growing Substratesmentioning
confidence: 99%